Study of Edge and Screw Dislocation Density in GaN/Al(2)O(3) Heterostructure - Ene, Vladimir Lucian (Materials (Basel), 2019)
This study assesses the characteristics (edge and screw dislocation density) of a commercially available GaN/AlN/Al(2)O(3) wafer. The heterostructure was evaluated by means of high-resolution X-ray diffraction (HR-XRD), high-resolution transmission electron microscopy (HR-TEM), and Doppler-Broadening Spectroscopy (DBS). The results were mathematically modeled to extract defect densities and defect correlation lengths in the GaN film. The structure of the GaN film, AlN buffer, Al(2)O(3) substrate and their growth relationships were determined through HR-TEM. DBS studies were used to determine the effective positron diffusion length of the GaN film. Within the epitaxial layers, defined by a [GaN [Formula: see text] (0 0 0 2) || [Formula: see text] AlN (0 0 0 2) || (0 0 0 2) [Formula: see text] Al(2)O(3)] relationship, regarding the GaN film, a strong correlation between defect densities, defect correlation lengths, and positron diffusion length was assessed. The defect densities [Formula: see text] 6.13 × 10(10) cm(−2), [Formula: see text] 1.36 × 10(10) cm(−2), along with the defect correlation lengths L(e) = 155 nm and L(s) = 229 nm found in the 289 nm layer of GaN, account for the effective positron diffusion length L(eff)~60 nm.